INNOVATIVE TECHNOLOGIES USED IN TEACHING BIOLOGY IN GRADES 7-8 OF SECONDARY SCHOOLS (Web of Teachers: Inderscience Research, 2026)
The process of teaching biology in grades 7-8 at secondary schools is undergoing significant changes in recent years, primarily due to the introduction and integration of innovative technologies. These technologies contribute greatly to making the educational process more effective, engaging, and tailored to the needs of modern students. The role of technology in education is becoming more pronounced as society progresses further into the information age, and the importance of preparing students for future challenges grows. Therefore, the use of innovative methodologies and tools in teaching such vital natural sciences as biology has come to the forefront of pedagogical efforts. Teachers today are searching for ways to move away from traditional, monotonous forms of delivering material, recognizing that students tend to better understand and remember information that is presented interactively and supports active participation. By leveraging various digital resources, multimedia content, and practical applications, educators create opportunities for effective learning, deeper understanding, and the development of logical thinking and scientific reasoning skills.